K. D. Balmont in the Reception of A. A. Izmailov - ALEKSANDROV, ALEKSANDR; ALEKSANDROVA, ELMIRA (Bulletin of Yerevan University H: Russian Philology, 2021)
This article is based on A. Izmajlov’s and K. Balmont’s correspondence (1907-1915). Izmailov is known as a gifted parodist of modernist literature. He reacted very negatively to the first experience of the emerging trends. Over time, his views on literary modernists products have undergone a certain evolution. This article provides an overview of critical reviews of the Balmont’s poetry. It allows to correct the widespread belief about Izmailov as an irreconcilable opponent of modernist literature.